Koordinierter Patentschutz in einer globalisierten Welt - Effizienz- und Anreizwirkungen auf die Arzneimittelversorgung in Entwicklungsländern - Kirsch, Michelle

Expertensystem zur Steigerung der Effizienz im Bereich der Produktion - Iwanek, Peter; Dumitrescu, Roman; Reinhart, Felix; Brandis, Rinje (productivITy (4 / 2015))

Economics and Value of IS - Han, K.; Kundisch, Dennis; Weinhardt, C.; Zimmermann, Steffen

Planungswerkzeug zur wissensbasierten Produktionssystemkonzipierung - Bauer, Frank

10. Paderborner Workshop Entwurf mechatronischer Systeme - Gausemeier, Jürgen; Dumitrescu, Roman; Rammig, Franz-Josef; Schäfer, Wilhelm; Trächtler, Ansgar

Vorausschau und Technologieplanung. 11. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 29. und 30. Oktober 2015 - Gausemeier, Jürgen

Just test what you cannot verify! - Czech, Mike; Jakobs, Marie-Christine; Wehrheim, Heike (Fundamental Approaches to Software Engineering)
Today, software verification is an established analysis method which can provide high guarantees for software safety. However, the resources (time and/or memory) for an exhaustive verification are not always available, and analysis then has to resort to other techniques, like testing. Most often, the already achieved partial verification results arediscarded in this case, and testing has to start from scratch.In this paper, we propose a method for combining verification and testing in which testing only needs to check the residual fraction of an uncompleted verification. To this end, the partial results of a verification run are used to construct a residual program (and residual assertions to be checked on it). The residual program can afterwards be fed into standardtesting tools. The proposed technique is sound modulo the soundness of the testing procedure. Experimental results show that this combinedusage of verification and testing can significantly reduce the effort for the subsequent testing.

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015; LNCS 9179)

Der Mensch als Vorbild - Trächtler, Ansgar; Iwanek, Peter; Scheffels, Gerald (elektrotechnik - Automatisierung Sonderausgabe)

Integrated Systems Engineering and Software Requirements Engineering for Technical Systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the International Conference on Software and Systems Process (ICSSP))
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and system models. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, for the discipline-specific development to start, these requirements need to be refined, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic transition from MBSE to model-based software requirements engineering, which we present in this paper. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach with an example of an automotive embedded system.

Planning and Optimisation of Manufacturing Process Chains for Functionally Graded Components – Part 2: Case Study on Self-reinforced Thermoplastic Composites - Biermann, Dirk; Gausemeier, Jürgen; Heim, Hans-Peter; Hess, Stefan; Petersen, Marcus; Ries, Angela; Wagner, T. (Production Engineering Research & Development 9(3))
In this sequel paper, the previously presented framework for the planning and optimisation of functionally graded components Biermann et al. (Production Engineering Research & Development 7(6):657–664, 2013) is applied within a case study. In addition to the application, the implementational infrastructure of the framework is provided and the preliminaries for applying the framework to the respective production system are presented. Hence, the practical realisation of the models and methods is documented. In the context of the case study, each step of the planning process is demonstrated in a visually assisted way. These visualisations are based on the specific steps of the wizard guiding the planner through the framework. As a central contribution, the specification of a non-trivial gradation and the planning of the corresponding process chain by means of the planning framework are demonstrated.

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Zustandsorientierte Modellierung flexibler Produktionssysteme - Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Stuttgarter Symposium für Produktentwicklung - SSP 2015)

Ontology-based determination of alternative CNC machines for a flexible resource allocation - Rehage, Gerald; Gausemeier, Jürgen (15th CIRP Conference on Modelling of Machining Operations (15th CMMO), Band 31)
In case of an unplanned machine breakdown, alternative resources have to be found quickly to avoid delays in following process steps. In order to counter this, an automated determination of alternative CNC-machines and a reliable validation is proposed. First, a rough process description is extracted from the NC program. Second, a suitable machine is searched in an ontology based on the rough process description. The ontology contains a description of all needed properties of a machine and rules to derive the resulting capabilities. Third, the NC program is validated on a virtual machine to ensure the absence of errors.

Vorsprung durch strategisches IP-Management - Gestiges Eigentum kennen, schützen und nutzen - Eckelt, Daniel; Gausemeier, Jürgen (IP: Kooperation, Wettbewerb, Konfrontation, 37. Kollequium der TU Ilmenau über Patentinformationen, Band 37)

Balancing the Strategic Product Portfolio based on Market and Competence Needs - Rübbelke, René; Söllner, Christoph; Gausemeier, Jürgen (24th International Association for Management of Technology Conference, Nr. 24)

Conception of a Knowledge Management System for Technologies - Placzek, Markus; Eberling, Christian; Gausemeier, Jürgen (24th International Association for Management of Technology Conference Proceedings, Band 24)

Tagungsband zum Stuttgarter Symposium für Produktentwicklung (SSP) - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

BUSINESS MODEL PATTERNS FOR DISRUPTIVE TECHNOLOGIES - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen (International Journal of Innovation Management 19(3))

HOW TO USE BUSINESS MODEL PATTERNS FOR EXPLOITING DISRUPTIVE TECHNOLOGIES - Echterfeld, Julian; Amshoff, Benjamin; Gausemeier, Jürgen (International Association for Management of Technology (IAMOT))